Characteristics of lime-hemp composite and its use in construction industry - Brzyski, Przemysław; Fic, Stanisław (Budownictwo i Architektura / Civil and Architectural Engineering, 2015)
One of the solutions for reducing energy consumption and carbon dioxide emissions in the construction sector is the use of building materials which have a favorable environmental impact. This is possible to achieve by using plant material, e.g., industrial hemp, which absorb large amounts of carbon dioxide during the growth. Instead of cement as a binder there are used alternatively clay or lime modified with industrial waste in the form of pozzolans. The paper presents the possibility of using industrial hemp in the production of composite based on modified hydrated lime. It describes the basic properties of the sample composites such as compressive strength and thermal conductivity based on literature review. The article describes the way of preparing the mixture and the possibility of using the composite for the construction of walls using different techniques.